Kikuchi Fujimoto Disease: The First Reported Case in Mongolia (Central Asian Journal of Medical Sciences, 2017)
Objectives: Kikuchi-Fujimoto Disease (KFD) is a rare, benign condition of necrotising histiocytic lymphadenitis, typically presenting in young women. This report is on the first diagnosed case of KFD in Mongolia. Methods: The patient was a 24-year-old female, who presented with fever, night sweats, rash, and cervical lymphadenopathy. Based on clinical features, histopathology, and immunohistochemistry findings, the diagnosis of KFD was confirmed. Results: Full recovery was achieved using symptomatic treatment. Conclusion: To minimize diagnostic confusion and potentially harmful and unnecessary treatments, we emphasize that clinicians should be aware of this condition.